Dagusibu And Pkrt Health Counseling In The Surrounding EnvironmentFor Wkri Dpd West Sumatra: Penyelenggaraan Kesehatan Dagusibu Dan Pkrt Di LingkunganLingkungan Rwkri Dpd Sumatera Barat - Reny Salim; Tuty Taslim; Irene Puspa Dewi; Fita Selonni (Journal of Community Service and Application of Science, 2022)
Mothers need knowledge of the treatment and use of PKRT according to the rules. This is important considering that the mother is the individual responsible for taking care of the family's needs. The expert must welcome the fulfillment of these mothers' needs must be received through devotional activities. One form of service activity that mothers can do is health counselling which aims to measure the influence of counselling on changes in participants' attitudes. The participants in this counselling are the categorial group of WKRI DPD West Sumatra The method used is offline and online interactive counselling. The supporting media used are Microsoft PowerPoint, Quiziz, and Zoom. The data collection method used is pretest-posttest. The results obtained in the counseling activity were a change in participants' attitudes before and after counseling with a signification value of p<0.05. It means that there is a need for interactive counseling on drugs and PKRT that can help improve public health and lower long-term adverse risks.